Bioconversion of pretreated wheat straw to ethanol by Monascus purpureus CBS 109.07 and Fusarium venenatum ATCC 20334 using simultaneous saccharification and fermentation - David Yudianto; ELLYAS ALGA NAINGGOLAN; Ria Millati; Chusnul Hidayat; Patrik Lennartsson; Mohammad J Taherzadeh; Claes Niklasson (Society for Indonesian Biodiversity, 2019)
Abstract. Yudianto D, Nainggolan EA, Millati R, Hidayat C, Lennartsson P, Taherzadeh MJ, Niklasson C. 2019. Bioconversion of pretreated wheat straw to ethanol by Monascus purpureus CBS 109.07 and Fusarium venenatum ATCC 20334 using simultaneous saccharification and fermentation. 20: 2229-2235. Fractions of sulfuric acid-pretreated wheat straw, i.e. solid, liquid, and a mixture of liquid and solid were used as substrates in simultaneous saccharification and fermentation (SSF) process to produce ethanol. The bioconversion was performed by Monascus purpureus CBS 109.07 and Fusarium venenatum ATCC 20334. The highest ethanol yields from solid, liquid and a mixture of solid and liquid fractions by M. purpureus CBS 109.07 were 0.36, 0.41, and 0.37 g/g glucose, respectively. The corresponding values by F. venenatum ATCC 20334 were 0.21, 0.54, 0.35 g/g glucose, respectively.